INTO THE NEXT NORMAL : PANIC ACADEMIC in the COVID-19 Pandemic - Chee-Ming Chan; Ismadiana Izika Albi; Aqilah Rahman; Fathiha Jalil (Penerbit UTHM, 2022)
Panic Academic in COVID-19 Pandemic, a collection of personal stories by 34 students from the class of Site Investigation (Semester 1 Session 2011/22), Faculty of Engineering Technology, UTHM. The illustrious stories tell of the students’ experiences, reflections and expectations throughout the pandemic lockdown period, which left a significant impact on their memories, studies and lives. Here we share their laughter, tears, doubts and uncertainties, but above all we find HOPE in their individually unique stories. Like a phoenix rising from the ashes, the hero or heroine in each story has certainly come out of the chaotic situation brought on by the COVID-19 pandemic better, stronger and more prepared to face the ever changing world.